The Integrative Paradigm of Sufi Psychology - Raja Bunga Sam Aji Putra Latuconsina; Ghozali Ghozali; Lydia Freyani Hawadi (Publikasi Indonesia, 2024)
The ontology and epistemology of Sufism are key elements in Islamic studies. Sufi psychology, as part of Sufism, essentially falls within the framework of Islamic psychology. This research aims to explore Sufi psychology and explore how these concepts can be integrated into modern psychological approaches. This research uses a qualitative method, with data collection through a literature study. The collected data were then analyzed through three stages: reduction, presentation, and conclusion. The results show that in logic, this relationship is known as the correlation between particularity and universality (al-Umum wa al-Khusus Mutlaqan). However, in its development, Sufi Psychology focuses more on esoteric aspects, perennialism, and inclusivism. Unlike Islamic psychology in general, Sufi Psychology has been developed by scholars outside the Islamic tradition, such as figures in transpersonal psychology, including Robert Frager (Chairman of the Institute of Transpersonal Psychology), Lynn Wilcox, James Fadiman, and Arthur Deikman. They develop the concept of tasawwuf by integrating Sufi knowledge with empirical contributions from modern psychology, resulting in a holistic approach to psychology, both in terms of ontology, axiology, epistemology, and methodology.